2023
DOI: 10.17221/291/2023-pse
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of carbon sequestration as affected by different management practices using the RothC model

Jakub Prudil,
Lubica Pospíšilová,
Tamara Dryšlová
et al.

Abstract: Long-term field experiments provide a valuable dataset for predicting changes in soil organic carbon (SOC) stocks in different agricultural systems. The RothC-26.3 model was used to simulate changes in SOC in the monoculture of spring barley (Hordeum vulgare L.) and the Norfolk crop rotation during 1972-2100. The potential of the Gleyic Fluvisol Clayic to sequester organic carbon was investigated. The studied soil was heavily textured, with medium organic carbon content. Four management scenarios in the monocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…So, determining the general regularities and drawing conclusions, researchers have to take into account specific local site conditions. Similar results were obtained by Prudil et al [26] who found that management with straw incorporation and inter-crops represented SOC increase during modelled different climate scenarios.…”
Section: Introductionsupporting
confidence: 89%
“…So, determining the general regularities and drawing conclusions, researchers have to take into account specific local site conditions. Similar results were obtained by Prudil et al [26] who found that management with straw incorporation and inter-crops represented SOC increase during modelled different climate scenarios.…”
Section: Introductionsupporting
confidence: 89%
“…Fields with cover crops would accumulate 0.28-0.33 Mg C ha −1 a −1 over 50 years [27]. Prudil et al [28] found that crop residues and the additional input of organic residues into the soil mainly influenced carbon stocks. The projection showed that soil carbon stocks decreased with monoculture.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Koga et al [35] concluded that not only manure application but also continuous C input to the soil through crop residue return is an essential practice for increasing C sequestration on an Andisol in northern Japan. Prudil et al [36] simulated changes in SOC in the monoculture of spring barley and the Norfolk crop rotation during 1972-2100 using the RothC-263.3 model. Results showed that SOC stocks of Gleyic Fluvisol were mainly influenced by plant residue inputs and exogenous organic materials' application.…”
Section: Effect Of Crop Rotation Complexitymentioning
confidence: 99%
“…SOC stock is indeed highly influenced by management practices, which can result in significant differences, sometimes even doubling the SOC stock under different management regimes. For example, Prudil et al [36] demonstrated that C sequestration for the monoculture of spring barley ranged from 40 to 66 t ha −1 . In contrast, the Norfolk crop rotation, which includes cereals, root crops, and forage crops, exhibited higher C sequestration levels, averaging approximately 70 to 100 t ha −1 .…”
Section: Carbon Sequestrationmentioning
confidence: 99%